From shelters to communities: Frederick Cuny's approach to disaster relief - Fraile-Garrido, Patricia; Martín-Robles, Inés (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2024)
This article examines the enduring influence of Frederick Cuny, a pioneering humanitarian whose work revolutionized disaster relief and refugee camp design. It explores Cuny's legacy in reshaping notions of permanence and temporality in camps, blurring the lines between these spaces and conventional cities. Cuny's approach challenged traditional rigid grid layouts, emphasizing community-based, decentralized designs that prioritized open spaces. His principles of community participation, development over aid, and the shift from shelter products to sheltering processes - ideas that the article links to the work of John F.C. Turner - continue to shape contemporary disaster management strategies. By examining two important case studies in which Cuny was involved, Camp Choloma and Program Kuchuba’l, the article also underscores the vital link between the spatial organization of camps and their social dynamics, emphasizing how camps evolve into permanent communities. Cuny's groundbreaking work remains highly pertinent in addressing modern challenges, including natural disasters, ongoing refugee crises, and substandard housing.
Keywords: Frederick Cuny; John F.C. Turner; refugees; camp planning; disaster relief; community participation; sustainable development